PRINSIP-PRINSIP MANAJEMEN VS KINERJA GURU: SEBUAH TINJAUAN UMUM - Sola, Ermi (Department of Islamic Education Management, 2022)
Abstract: Principles of Management VS Teacher Performance: An Overview Education is an absolute necessity throughout life. Schools are formal educational institutions as one of the central points of education and learning. The quality of education in each school is different. This happens because of different managerial strategies in managing school resources. The quality of the education and learning process can be viewed from two aspects, namely the quality of the components and the quality of school management. Although the supporting components such as the availability of adequate facilities and infrastructure and sufficient funds, if they are not managed